Uncertainty Based Information On Fuzzy Sets - Kumud Borgohain (Elementary Education Online, 2023)
This paper deals with a study on the Fuzzy theory with the probability theory which is also used to express uncertainty. The concept of fuzziness is introduced in order to measure the uncertainty of fuzzy set. We will discuss various forms of uncertainty and possibility, fuzzy measures such as belief, plausibility, possibility and probability measures , possibility distribution and fuzziness.